A study of centralization of library and information services at the Philippine Sugar Commission - David, Prescy S.; Aquino, Leticia E.; Hidalgo, Namnama P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1980)
The Philippine sugar industry, in spite of its many problems and recent reverses in the world market, is still one of the pillars of the country's economy. The nation has continued to maintain its position as the fourth largest exporter of sugar in the world.
In the face of fast changing developments in technology and in manufacturing and marketing techniques spurred by well-funded research in the developed countries, the Philippine sugar industry must modernize and keep up with current trends in order to continue playing a major role in the nation's economy. The government, aware of the situation, has established various agencies like the Philippine Sugar Institute (PHILSUGIN), the Sugar Quota Administration (SQA), and the sugar marketing division of the Philippine Exchange (PHILEX), a subsidiary of the Philippine National Bank. These agencies were absorbed lately into the Philippine Sugar Commission (PHILSUCOM) which is tasked with the management, rationalization and guidance of the sugar industry. To support this big effort, an efficient system of information retrieval within the governement sugar agency needs to be set up. Voluminous literature and data on researches and studies in the Philippines and around the world must be acquired and classified under a system that will assure easy retrieval where and when needed.
To answer this need, a system to be known as the Philippine Information Network for Sugar (PINETS) is to be established with the PHILSUCOM Main Library as the Center Node and the libraries of the three branches as Regional Nodes. The Regional Nodes shall in turn serve other branch and station information centers within their respective regions. The whole sugar network shall, on the upper level, coordinate with international information networks thus making available to all sectors of the sugar industry the world's information resources.
All libraries and information centers that will become part of the network shall remain within the control of their respective organizations. The network shall be no more than a flexible grouping of member-libraries coordinating and cooperating towards a definite objective. Information on the collection of the entire network shall be centralized and included in the Union Catalog of the Center Node. Personnel qualifications, operational procedures, and physical set-ups shall be standardized according to set guidelines.
Thus organized, PINETS, like counterpart networks in other disciplines here and in other countries, may help significantly to move the sugar industry closer to its goals.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Library information networks--Philippines.; Philippine Sugar Commission. Library; Sugar industry--Philippines.